The Implementation of the Behavioral Remedial Program at Homeschooling: A Case Study at Homeschooling Kak Seto in Indonesia - Herlina Siregar; Rahmawati Rahmawati; Mokete Nyaphisi Bendly (Universitas Sultan Ageng Tirtayasa, 2022)
This study aimed to describe the implementation of the behavioral remedial program at Homeschooling Kak Seto in Indonesia. This research was conducted at Homeschooling Kak Seto, which is located at Jl. Raya Perigi Lama No. 3A Perigi, Pondok Aren, South Tangerang City-Banten, Indonesia with the informants including the head of special education, tutors, and parents of students. The research method used is descriptive method with a qualitative approach in order to be able to collect, compile and analyze the results. Data collection technique consisted interviews, observation and documentation. The steps of this research went through the orientation, exploration, and member check stages. Techniques for processing and analyzing data in this study were data reduction, data presentation, and drawing conclusion. The data validity technique in this research is credibility, transferability, dependability, and confirmability. Based on the results of the study, it was concluded that the application of the behavior remedial program to changes in the social skills of learning citizens with special needs at Homeschooling Kak Seto was in accordance with the theory of behavior modification, namely through the process of antecedent, behavior, and concequence.